Ketogenic Diet Overview: Downsides May Outweigh Benefits - Nowocień, Paula; Kordylewska-Kubus, Angelika; Paszkiewicz, Iga; Nowocień, Dominik; Wróbel, Marta (Quality in Sport, 2026)
Introduction: Due to the growing problem of high mortality and incidence of civilization diseases, including metabolic syndrome and obesity, there is an urgent need to find effective ways to prevent it. The purpose of this study was to review the effects of a ketogenic diet on particular systems and organs, as well as to analyze possible associated risks. Methods: Systematic review and current research about the impact of Ketogenic Diet to different systems was made. Authors wanted to highlight pros and cons of conveying this type of nourishment. Results: Consequently, there has been an increased focus on a healthy diet. Mass media allow access to abundant information on the purported beneficial effects of various diets, whether it is a weight loss diet, a cleansing diet, or a diet aimed at supporting the functioning of individual organs. The Ketogenic Diet is one of the most frequently used nowadays. It significantly reduces carbohydrate intake to just 5-10% of the total calorie consumption in favor of approximately 55% to 60% fat intake. According to previous research, we should emphasize the fact that conducting this type of diet can reveal many side effects. Conclusion: Despite the advantages of the diet for people suffering from obesity and diabetes mellitus type 2, for most individuals it results only in temporary improvements and an increase of unfavorable effects. Overall, according to our research, the risks of the ketogenic diet might outweigh its benefits. The Ketogenic Diet is an example of a nutrition trend that should not be used on such a large scale.